Basic peculiarities of energy band spectra within generalized kindal's model for semiconductors with one main axis - Chuiko, G.P.; Martyniuk, V.V.; Bazhenov, V.K. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
The analysis of the basic features of the generalized Kildal model had been presented for the semiconductors without the center of symmetry and with one main crystal axis. It had been proved, that the Kramers’ degeneration survives only along and against of the direction of the main crystal axis and at point Γ ( 0=k ) within this model under the condition of the absence of the center of symmetry, as rule. The Kramers’ degeneration is possible everywhere, although only for the band of the heavy holes like within Kane’s model, even under the previous condition, but only if casually takes place the special relation between parameters. The typical set of solutions within this model consists of one conductivity band ( 0≥ε ) and of three valence bands ( 0≤ε ). Each of them contains two spin subbands. The additional conductivity band would be possible in principle, but only under special condition ( 0<δ ), which is the obligatory but not enough condition.